FUNDAMENTALS OF ADMINISTRATIVE SETTLEMENT OF CUSTOMS OFFENSES - Кунєв, Юрій Дем’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article is to formulate proposals on the possibility of achieving the goal of administrative penalty under art. 23 of the Code of Ukraine on Administrative Offenses on the basis of the problems analysis of the Customs Code of Ukraine. Research methods: system analysis and synthesis, comparative legal and doctrinal cognition of customs legislation; methods of comparison and comparing the provisions of international and national customs legislation, as well as the method of generalization and modeling of new theoretical knowledge. Results: problems of further development of administrative settlement of customs offenses are defined and certain ways of their decision are offered. The properties of customs legislation are determined by the quality of the general rule of law in relation to the regulatory and security components. The main problems in the field of protection of regulatory norms is that the regulatory norm should be part of the disposition of the protective norm. The general regulation of the whole sphere of activity depends on the quality of the regulatory norm. To systematically solving of all the identified problems, it is necessary to link security to regulations and the division of misdemeanors by specific customs procedures for the movement of goods, which, in turn, can also be grouped by general procedures: import, export and transit. Discussion: argues that all existing articles of customs legislation should be checked for compliance with the constitutional principles of responsibility and standards of responsibility in the customs sphere, set out in international treaties and agreements ratified by Ukraine. The properties of legislation in general are determined by the quality of the general legal norm in connection with the regulatory and protective components. The quality of general protective norms is more stable in historical and organizational terms for the existence of many years of total penal law. There are many problems, both theoretical and practical, regarding the quality of regulatory norms and their legal protection. The main problems in the field of protection of regulatory norms is that the regulatory norm should be part of the disposition of protection, and the quality of the regulatory norm depends on the general regulation of the entire sphere of activity. In the next publication we will consider separately the quality of the protection norm through the quality of the regulatory one, as they are components of the general norm of regulation of activity in the customs sphere and activity according to its separate components - customs procedures. We will study the problems of administrative liability on the example of the analysis of the content of the provisions of the articles of the Customs Code of Ukraine.